2015
DOI: 10.1038/ajg.2015.356
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Diabetes Mellitus after First-Attack Acute Pancreatitis: A National Population-Based Study

Abstract: The risk of diabetes increases by twofold after AP; therefore, a long-term screening is necessary to evaluate diabetes after an attack regardless of severity. Further research should be conducted to develop cost-effective follow-up strategies, and to elucidate the underlying mechanisms of the relationship between diabetes and AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 35 publications
6
88
0
Order By: Relevance
“…An example of the translational importance of the latter is highlighted by the recent recognition that pancreatic islet β-cell failure may be seen as a late complication in 20%–30% of acute pancreatitis 77 . Differences in the microbiota, metabolism, diet, and regulation of inflammation can be substantial between human beings and rodents and affect disease mechanisms and phenotypes.…”
Section: General Mechanisms Values and Limitations Of Models And Stmentioning
confidence: 99%
“…An example of the translational importance of the latter is highlighted by the recent recognition that pancreatic islet β-cell failure may be seen as a late complication in 20%–30% of acute pancreatitis 77 . Differences in the microbiota, metabolism, diet, and regulation of inflammation can be substantial between human beings and rodents and affect disease mechanisms and phenotypes.…”
Section: General Mechanisms Values and Limitations Of Models And Stmentioning
confidence: 99%
“…Moreover, a large population-based study showed that patients after AP have a 2.5 times higher risk of developing newly diagnosed DM than individuals in the general population (32). Surveillance of high-risk patients with AP for prediabetes or diabetes would appear advisable (11,32).…”
Section: Msmentioning
confidence: 99%
“…A recent comprehensive systematic review and meta-analysis of prospective clinical studies (11) showed that abnormal glucose metabolism (AGM) after an episode of AP is present in nearly 40% of patients without history of DM. Moreover, a large population-based study showed that patients after AP have a 2.5 times higher risk of developing newly diagnosed DM than individuals in the general population (32). Surveillance of high-risk patients with AP for prediabetes or diabetes would appear advisable (11,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While its statistics were, until recently, largely confined to chronic pancreatitis and pancreatic cancer (3,4), emerging large scale population-based studies show that more than 60% of all cases of diabetes of the exocrine pancreas are due to new-onset diabetes after acute pancreatitis (NODAP) (5)(6)(7), and that the risk of NODAP may not depend on severity of acute pancreatitis (8,9). However, the molecular mechanisms underlying the pathophysiology of NODAP remain unclear.…”
Section: Introductionmentioning
confidence: 99%